Jose van den Besselaar (1916-1991) and his Propylaeum Latinum - Beccari, Alessandro [UNESP] (Univ Federal Parana, Editora, 2021)
The main objective of this article is to present a brief initial outline of the biography of the Dutch latinist, historian and lusitanist Jose van den Besselaar (Josephus Jacobus van den Besselaar (1916-1991)) and some aspects of his contribution as the author of the Propylaeum Latinum: sintaxe latina superior (1960), in which the Dutch grammarian undertakes analyzes based on a Germanic strand of Traditional Grammar and uses notions and procedures derived from Historical and Comparative Linguistics. Moreover, this article aims to carry out a first discussion of the ideas and procedures contained in the Propylaeum Latinum taking into account its relevance for a historiography of the teaching of the advanced contents of Latin syntax to speakers of Brazilian Portuguese. Besselaar's work is also compared to that of other grammarians who either were his contemporaries or were mentioned by him, as Rubio (1966), Ernout and Thomas (1953), Tovar (1946) and Palmer (1954) in order to identify to what extent there would be continuities and/or innovative proposals in Besselaar's approach in contrast to other grammarians. The following notions from Linguistic Historiography or The History and Philosophy of Science form the guidelines for the historiographical analysis: the relativity of scientific theories (KUHN, 2009 [1963]), scientific research as a non-autonomous and rhetorically controlled activity (MURRAY, 1989), the continuities and discontinuities foreseen in the models and principles of Koerner (1989), the research programs proposed by Swiggers (2004).
Keywords: Jose van den Besselaar; Latin Syntax; Linguistic Historiography